Optimization of Production Methods for Black Soldier Fly Larvae (Hermetia illucens L.) in Burkina Faso - Florence Sankara; Fernand Sankara; Salimata Pousga; Kalifa Coulibaly; Jacques Philippe Nacoulma; Zakaria Ilboudo; Issoufou Ouédraogo; Irénée Somda; Marc Kenis (Insects, 2023)
Larvae of Hermetia illucens are a valuable source of protein for animal feed that can be produced by exposing animal and agro-industrial wastes to naturally occurring flies. The objective of this study was to improve techniques for obtaining H. illucens larvae to feed livestock in Burkina Faso. An experiment was conducted to determine the most favourable substrates and seasons for larval production. The substrates used were poultry manure, local beer waste, local beer waste mixed with poultry manure, cottonseed cake, and industrial brewery waste mixed with poultry manure. The production of larvae was carried out in four different seasons. The effect of the container’s oviposition area (0.07 m2, 0.09 m2, and 0.11 m2) and the type of container (terracotta, plastic, and iron) on larval production was also assessed. The produced larval biomass was high during, or just after, the rainy season but very low during the cool dry and hot dry seasons. Yields were higher with local beer waste mixed with poultry manure followed by local beer waste and cottonseed cake. The average mass of H. illucens larvae increased slightly with the oviposition area for the same amount of substrate. Iron and terracotta containers provided better results than plastic containers. The suitability of this production method for H. illucens larvae production is discussed.